(untitled) (International Journal of Physiotherapy, 2017)
Background: Neck pain has been reported as a prevalent musculoskeletal disorder globally with more than half of the general population being affected once or more within their life span. Methods: A randomized clinical trial research design was used which investigated the immediate effect of cervical manipulation on neck pain and cervical range of motion among patients with chronic mechanical neck pain. 20 male and female participants between the ages of 26 to 60 years with chronic mechanical neck pain attending physiotherapy clinics were recruited. They were randomly assigned into two groups (A and B) of 10 patients each. Group A received soft tissue massage, and cervical manipulation and group B served as the control group, and they received only soft tissue massage. There were two outcomes measured; Pain intensity was rated using visual analog scale (VAS) before and immediately after the intervention. Pre and Post intervention measurements of cervical spine range of motion using Goniometer were also taken. Results: Findings of the study revealed significant immediate improvement of pain and Cervical Range of Motions (p<0.05) in all dimensions in the experimental group while Pain, flexion and right side Cervical flexion significantly improved in the control group. It was also found out after comparing the outcomes between the two groups that, the experimental group had significantly (p<0.05) better improvement than the control group in post-intervention pain, cervical flexion, cervical extension and cervical (right and left) lateral rotations. Conclusion: Cervical manipulation is effective in immediate pain relief and improvement in cervical range of motion in patients with mechanical neck pain.